Indigenous Youth Mental Health in Canada: A WPR Approach to Canada’s (In)Action in Response to Suicide Crises - Victoria, Francavilla (2020)
Major Research Paper (Master's), Health, Faculty of Health, School of Health Policy and Management, York University Across Canada, Indigenous Peoples have been resilient to active colonization for more than 400 years, all the while upholding their traditional values, systems, and ways of being. However, despite this resilience, Indigenous youth experience disproportionate and elevated rates of negative mental health outcomes, including elevated rates of suicides. Canadian mental health policy has not been responsive to the needs of Indigenous youth, often ignoring the specific needs of Indigenous communities in documents that are meant to guide programming and responses. In this Major Research Paper (MRP) I review one such key document -the Mental Health Commission of Canada's (MHCC) 2016 recommendations in its report titled The Mental Health Strategy for Canada: A Youth Perspective. This document is the broadest reaching and most current official document addressing the issue of First Nations, Inuit, and Métis (FNIM) youth mental health at a Federal level. By analysing the narrative used throughout this document one can learn how the solutions proposed may actually be failing to address the root causes of the issue at hand. Using Carol Bacchi’s WPR (What’s the Problem Represented to be?) approach, it will become evident as to why these responses are not wholly conducive to achieving better mental health outcomes for Indigenous youth. Following this discussion, I will highlight the progress that is being made in various Indigenous communities in a variety of culturally relevant, safe, and sensitive ways. Communities who are thriving and who are working towards positive change for youth are the experts in this case, as they have the knowledge and are taking up practices which are created from themselves, not for them. These practices have the potential to influence policy, as they are paving the way for a better response in cases of Indigenous youth suicide. When systems are put in place that truly benefit the ...